RESTRUCTURING OF CONSUMER FINANCING AGREEMENTS DURING THE COVID-19 PANDEMIC - SRI ASTUTIK (Sekolah Tinggi Ilmu Hukum Awang Long, 2020)
Corona Virus Disease 2019 (Covid-19) has an impact on weakening the ability of debtors to meet their obligations to pay loan installments to financial institutions. This research was conducted with the aim to find out government policies in providing solutions to the weakening of the performance of financial institutions due to the Covid-19 pandemic, due to the lack of certainty of debtors in repaying their loans. Normative juridical research with a statute approach is carried out by gathering legal material through literature studies and internet searches. The results of the analysis of legal materials, that to restore business prospects in the field of finance companies that were affected by Covid-19, related to the real sector, economic growth and debtor performance, the government issued the Financial Services Authority Regulation (POJK) Number 11 / POJK.03 / 2020 concerning the Banking Stimulus National Policy as Countercyclical Impact of Corona Virus Disease 2019, by restructuring financing by: Reducing interest rates, extending the period, Reducing principal arrears, Reducing interest arrears or Conversion of credit / financing into temporary equity participation.